International Multi-Conference on Systems, Sygnals &Amp; Devices 2012
DOI: 10.1109/ssd.2012.6198017
|View full text |Cite
|
Sign up to set email alerts
|

MEMS acoustic emission sensor with mechanical noise rejection

Abstract: The presented paper describes the use of a new approach to develop a high frequency acceleration sensor with good low frequency noise rejection and in contrast to conventional resonant sensors a short settling time, as it is needed for acoustic emission testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…the base capacitance C 0 . In contrast, configurations of mechanically un-coupled sensor-arrays that are connected in parallel in the electrical domain (similar to [12]) achieve an increased signal by a higher base capacitance C 0 of the system (see also Supporting Information). This distinction may prove beneficial for certain system aspects, such as read out circuits and energy efficiency.…”
Section: A Performance As Mechanical Filtermentioning
confidence: 99%
See 1 more Smart Citation
“…the base capacitance C 0 . In contrast, configurations of mechanically un-coupled sensor-arrays that are connected in parallel in the electrical domain (similar to [12]) achieve an increased signal by a higher base capacitance C 0 of the system (see also Supporting Information). This distinction may prove beneficial for certain system aspects, such as read out circuits and energy efficiency.…”
Section: A Performance As Mechanical Filtermentioning
confidence: 99%
“…For more information, see http://creativecommons.org/licenses/by/3.0/ using an array of transducers with different frequencies by Ozevin et al [6]. Alternatively, Sorger et al [11] and Auerswald et al [12] obtained an electro-mechanical bandpass characteristic by exploiting the phase shift between two separate oscillators of different resonance frequency. The disadvantage of relying on resonance for increasing the devices sensitivity are long settling times of the transducer which can lead to undesired downtime in-between the detection of AE/MS events.…”
Section: Introductionmentioning
confidence: 99%
“…9 In view of the successful cases of CMUTs in medical applications, many scholars started to seek applications of CMUTs in the field of structural health monitoring (SHM). [10][11][12][13][14][15][16] The acoustic emission (AE) technique, known as the SHM method of capturing and processing the stress-wave signals (usually between 100 kHz and 1 MHz 10 ) rapidly released during the development of structural damages, e.g., cracks, 17 delamination, 18 and fatigue, 19 could diagnose the damage status of structures in service. Transducers are one of the key components of data acquisition in AE systems.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, many verification studies have been carried out to show the feasibility of applying CMUTs in SHM. [10][11][12][13][14][15][16]24,25 For instance, Ozevin et al 10 demonstrated the possibility of using CMUTs by simulating AE events on a pre-cracked rectangular steel beam specimen. Hossain Saboonchi et al 13 used the MetalMUMPs technique to design and realize CMUTs with high aspect ratio geometry, the sensitivities of which are comparable to the piezoelectric ones.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments show that the sensitivity of MEMS sensors (8.8×10 7 (V/m)) is about 50 times higher than that of the traditional piezoelectric AE sensor at atmospheric pressure. In 2012, Auerswald et al [5] designed a comb-like driving AE sensor using the principle of capacitance change, but the sensor sensitivity is poor. In the studies on acoustic emission sensors, the resonant capacitance sensors studied by most scholars have low Q and sensitivity (for example, for the traditional perforated plate, Q = 2 when frequency f =182kHz).…”
Section: Introductionmentioning
confidence: 99%